Earthly temptations and practice of compassion in the works of Xu Dishan - Te, Ah Theen (2015)
Xu Dishan (1894 – 1941) was a May Fourth Movement activist, scholar of religious studies, social activist and prolific writer who wrote under the pseudonym Luo Huasheng. Unlike many other writers, his works featured both love stories of exotic lands and Buddhist teachings. During his short life of 49 years, filled with episodes of great passion, he viewed desires as the origin of sufferings and lamented the “endless sufferings in life”. Xu wrote about the pains and sufferings of life from the Buddhist perspective of earthly temptations and compassion, and his writings were attempted to explore the impermanence of life as well as the value of life. His efforts helped inject new literary themes into modern literature, inspired more writers to explore Buddhism in their writings and ultimately helped create a new and unique theme in literature. Hardship and suffering were Xu’s constant companions throughout his short life and these experiences were depicted in his works. During his early years, he devoted himself to the study of religions and moulded his ideologies with writings about “life”. In his later years, he shifted his focus to literary and artistic works, education outreach programme and the training of young talents in literature. All these efforts were tightly linked to his compassionate nature. As a central force that drove Xu’s achievement and contribution, his views on compassion is a subject worthy of scholastic research. This thesis aims to explore Xu’s literature and scholarly writings from the point of view of tainted love and untainted love, and to analyse elements of Buddhism in his works,which include earthly temptations as well as the central Buddhist tenet of compassion that reduces pain and induces happiness. This study will explore how Xu projected his views on the topics of earthly temptations, compassion and endless sufferings in life through his fictional characters, in particular, such sufferings in life as were manifested in their thoughts, personalities and conducts. In addition, this thesis will also explore the presence of the Five Perfections in Xu’s works and his spirit in encouraging the moulding of an ideal personality. This thesis is divided into five chapters. Besides the introduction and the conclusion,three areas will be explored. Firstly, the author will explore Xu’s literature thoughts and the influence of Buddhism in his life. The author will briefly introduce Xu’s lifestyle and works, then analyse the reasons behind Xu’s Buddhist inclination and interpret some of the Buddhist ideologies within his works. Next, the author will explore the relation between the earthly temptations and endless sufferings in life implicit in his “tainted love” series. This chapter is further divided into two sections. The first section looks at the issues from the point of view of man-woman, parentschild,power and influence, fame and wealth, and social standing to further understand how Xu depicts life’s sufferings through the earthly temptations. The second section looks at virtues such as greed-less, anger-less and obsession-less, to gain an insight into how Xu was able to transcend suffering through untainted love. Finally, the thesis explores compassion implicit in his “untainted love” series from the perspective of the Five Perfections (generosity, discipline, tolerance, diligence, wisdom). The thesis also analyses how the characters in Xu’s work practise compassion through the 5 virtues.